2008
DOI: 10.1111/j.1365-2559.2008.03042.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1‐positive diffuse large B‐cell lymphoma

Abstract: 992-996. 7. Lucendo AJ, Navarro M, Comas C et al. Immunophenotype characterization and quantitation of the epithelial inflammatory infiltrate in eosinophilic esophagitis through stereology. Am. J. Surg. Pathol. 2007; 31; 598-606. 8. Aceves SS, Newbury RO, Dohil R et al. Distinguishing eosinophilic esophagitis in pediatric patients. Clinical, endoscopic and histological features of an emerging disorder. J. Clin. Gastroenterol. 2007; 41; 252-256. 9. Kagalwalla AF, Shah A, Ritz DS, Melin-Aldana H, Li B. Cow's mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 10 publications
(17 reference statements)
1
35
0
Order By: Relevance
“…In the literature, there are three reports containing 12 cases of cyclin D1-positive DLBCL (Table 1) [3][4][5]. FISH studies demonstrated absence of the t(11;14) translocation in 11 of the 12 cases.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the literature, there are three reports containing 12 cases of cyclin D1-positive DLBCL (Table 1) [3][4][5]. FISH studies demonstrated absence of the t(11;14) translocation in 11 of the 12 cases.…”
Section: Discussionmentioning
confidence: 94%
“…Ehinger found that 10 (4.3%) of 231 cases of DLBCL cases were positive for cyclin D1 and none were positive for CD5. Rodriguez-Justo and Teruya-Feldstein each presented a case of cyclin D1-positive DLBCL [3,4]. Comparison of these 12 cases show that, excluding the misdiagnosed MCL, either Bcl-6 or MUM1 was expressed [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of CD5 was not exclusively associated with any morphologic subtypes (8). Cyclin D1 which is a cell regulatory protein that aberrantly expressed in MCL as a result of the t (11; 14) (q13; q32) / CCND1 -IGH (9). Almost all cases of MCL are moderately to strongly positive for CyclinD1 and the neoplastic cells often show minor variation in staining intensity that most likely correlate with the phase of cell cycle (highest at G1 → S phase).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to MCL, cyclin D1 can be detected in a subset of cases of CLL / SLL, hairy cell leukemia and plasma cell myeloma. Also few studies showed Cyclin D1 expression by diffuse large B cell lymphoma (9). In this condition differentiation between diffuse large B cell lymphoma and aggressive MCL is difficult and molecular study for t (11;14) (q13; q32) / CCND1 -IGH is helpful.…”
Section: Discussionmentioning
confidence: 99%